A low cost MEMS based NDIR system for the monitoring of carbon dioxide in breath analysis at ppm levels - Vincent, T.A.; Gardner, J.W. (Sensors and actuators. B, Chemical, 2016)
•MEMS based NDIR system for ppm CO2 detection with lock-in amplifier.•Fast 1.3s response time for breath-by-breath analysis.•Portable breath analyser designed for measuring metabolic rate of subjects.•Effect of path length on NDIR system investigated with novel sensor housing.•Silicon on insulator IR emitter used for low power, low cost gas detection. The molecules in our breath can provide a wealth of information about the health and well-being of a person. The level of carbon dioxide (CO2) is not only a sign of life but also when combined with the level of exhaled oxygen provides valuable health information in the form of our metabolic rate. We report upon the development of a MEMS-based non-dispersive infrared CO2 sensor for inclusion in a hand held portable breath analyser. Our novel sensor system comprises a thermopile detector and low power MEMS silicon on insulator (SOI) wideband infrared (IR) emitter. A lock-in amplifier design permits a CO2 concentration of 50ppm to be detected on gas bench rig. Different IR path lengths were studied with gases in dry and humid (25% and 50% RH) in order to design a sensor suitable for detecting CO2 in breath with concentrations in the range of 4–5%. A breath analyser was constructed from acetal and in part 3D printed with a side-stream sampling mechanism and tested on a range of subjects with two data-sets presented here. The performance of the novel MEMS based sensor was validated using a reference commercial breath-by-breath sensor and produced comparable results and gave a response time of 1.3s. Further work involves the detection of other compounds on breath for further metabolic analysis and reducing the overall resolution of our MEMS sensor system from ca. 250ppm to 10ppm.